PEMBAHARUAN PENGELOLAAN ZAKAT - Moch. Yazid Afandi (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2011)
Zakat is a community-empowering institution that is supported by values of spiritualitySpirituality on zakat should give inspiration of steadiness and sincerity to the Muslims whohave more wealth to empower people who are economically disadvantaged. So, Islam as aliberating religion can easily perform the liberation and empowerment of society from ignorance,poverty, and underdevelopment. Zakat, in the present day, will be much more effective if it ismanaged with modern management and imposed on all wealth that is legally acquired.